International Code of Phytosociological Nomenclature. 4th edition - Theurillat, Jean‐Paul; Willner, Wolfgang; Fernández‐González, Federico; Bültmann, Helga; Čarni, Andraž; Gigante, Daniela; Mucina, Ladislav; Weber, Heinrich; Chytrý, Milan (Applied vegetation science, 2021)
The fourth edition of the International Code of Phytosociological Nomenclature (ICPN) was prepared by the Steering Committee of the IAVS Working Group for Phytosociological Nomenclature (GPN). The edition consists of 14 Definitions, 7 Principles, 53 Articles, and 7 Appendices. When compared with the previous edition, the main amendments are: (a) the acceptance of electronic publications (Art. 1); (b) the introduction of binding decisions (Definition XIV, Principle II, Articles 1, 2b, 3c, 29b, 40, 42, 44, Appendices 6 and 7); (c) the mandatory use of the English or Latin terminology for syntaxonomic novelties (Definition II, Principle II, Articles 3d and 3i); (d) the introduction of autonyms for the main ranks when the corresponding secondary ranks are created (Articles 13b and 24); (e) the automatic correction of the taxon names (name‐giving taxa) used in the names of syntaxa in accordance with the International Code of Nomenclature for algae, fungi, and plants (ICN) (Article 44); (f) the possibility to mutate the name of a syntaxon in using other correct, alternative names for the name‐giving taxa (Article 45); (g) the introduction of inadequate names, a new category of rejected names (Definition V, Articles 43 through 45); and (h) the introduction of a conserved type (Definition XIII, Article 53). The fourth edition of ICPN was approved by the GPN on 25 May 2019 and becomes effectively binding on 1 January 2021. The new edition of the ICPN will become effectively binding on 1 January 2021. It consists of 14 Definitions, 7 Principles, 53 Articles, and 7 Appendices. Some Articles bring important amendments, among which the acceptance of electronic publications or the possibility to request a binding decision on controversial cases.